Impact of Entrepreneurial Performance of Small Medium Hotels; the Basis for Industrial Clusters in Western Region of Ghana - Xuhua, Hu; Kwofie, Adelaide Spio-; Addai, Michael; Mensah, William Gyasi- (IJRDO - Journal of Applied Management Science, 2016)
This study talks about entrepreneurial performance of small medium hospitality industry andthe impact it will bring to Western Region of Ghana if the hotel industry is clustered.Although there is an increase in knowledge that Small Medium Enterprises are centre ofevery industrial improvement, systematic plan of action aimed at supporting the SMEs havemost often fail. Successful stories about SMEs exist but are rare and this causes pauses forconcern. Many researchers have established that industry cluster brings several benefits effectin countries that are industrialized. The table indicates that the respondents totally agree thatan entrepreneur performance is better in relation to one’s determination to achieve, goodcustomer service, initiative ability, possess no fear of failure attitude, cope comfortably withnew situations and strong emphasis on the marketing of tried and true products and servicesare some of the strength of an entrepreneurs in Western Region. The study further revealedthat, with a significant value of 0.00 at 5% significance level, the dependency of being able torecover one’s start-up money on the source of the start-up money is justified. Therefore,taking into consideration the benefit associated with industry cluster, hospitality industries inWestern Region stand to gain if cluster policies are implemented.